THE URGENCY OF SHARIA LAW IN THE FORMATION OF INTERNATIONAL TRADE CONTRACTS BASED ON THE BLUE ECONOMY - Khoiruddin, Amir (Program Studi Magister Hukum Universitas Malikussaleh, 2025)
This study examines the urgency of applying Sharia law in the formation of international trade contracts based on the principles of the blue economy. Sharia law emphasizes justice, transparency, and ethical business conduct values that are increasingly relevant in the development of sustainable marine-based trade practices. As global trade intensifies, integrating Sharia principles into international contracts faces notable legal challenges due to the diversity of legal systems among countries, including civil law, common law, and hybrid systems. Using a normative juridical method and applying conceptual, statutory, and sociological approaches, this research explores practical mechanisms for incorporating Sharia law into international contracts, such as through choice of law clauses, Sharia-compliant arbitration forums, and harmonized legal frameworks. The study also analyzes the role of Indonesia’s national regulations specifically Law Number 7 of 2014 on Trade and Law Number 17 of 2008 on Shipping in facilitating Sharia-compliant maritime trade, alongside the strategic position of the Organization of Islamic Cooperation (OIC) in promoting cross-border legal harmonization. Findings indicate that the integration of Sharia law into international trade contracts not only reinforces ethical and sustainable economic governance but also offers a viable model for inclusive and equitable global commerce in alignment with the core values of the blue economy. Keywords: Sharia Law, International Trade Contracts, Blue Economy, Legal Harmonization, Islamic Law.